Microgrids dynamic stability interconnected through low voltage AC network - Vinit Kumar Singh; Ashu Verma; T. S. Bhatti (International Journal of Applied Power Engineering (IJAPE), 2021)
Renewable energy based microgrids have main challenges of maintaining its frequency-voltage characteristics and system becomes more complex when they are interconnected. These sources being intermittent in nature need to be supported by other resources like diesel/biogas such that at time of small variation in load or natural sources (wind/solar), power requirement is met through support provided by diesel/biogas-based system. Also, the controller should be fast enough to minimize the changes such that system reaches steady state. In this paper, renewable based rural microgrid consisting of wind, solar and biogas is modeled and interconnected through low voltage AC (LVAC) line. Also, one of the microgrid modeled is connected to the main grid as well as drawing power from the other microgrid. Control approach have been developed in such a way that whenever there is disturbance in the system due to increase/decrease in load or input to the renewable energy sources the biogas-based system of individual microgrid increases/decreases its generation to support the system requirement. No extra power is drawn either from the LVAC network or main grid as desired. modeling of system and its dynamic Study has been carried out in MATLAB/Simulink.